Management Policies Implication for the Agricultural Land Conversion Sustainable Control Strategy in Bali Province - SUARDI, I Dewa Putu Oka; WIDHIANTHINI, Widhianthini; ARISENA, Gede Mekse Korri; SUYARTO, Raden; KRISNANDIKA, Anak Agung Keswari (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).12, 2022)
The conversion of agricultural land to non-agricultural-purposes land had occurred in almost all areas in the Bali Province. This study aimed to explore sustainable food agricultural land control strategies in the Bali Province, by involving stakeholders: farmers, subak institutions, local agricultural board, agricultural business actors, agricultural financial institutions, NGOs, universities, and agricultural research and development bodies as study participants. SWOT analysis and Interpretive Structural Modeling (ISM) are used to analyze study data. The findings showed that the short, medium, and long-term strategies have great potential and are in line with some management policies to control the agricultural land sustainable conversion in the Bali Province. This strategy may bring essential changes for several areas: stimulating agricultural development policy formulation that align with Balinese local wisdom values, leading to a more selective agricultural land investment choice, procurement of special fund for legal protection of staple food agricultural land, and strengthening local to national-scale agricultural institutions.